The Effect Of Portfolio Assessment-Based Pjbl Model On Students' Critical Thinking And Creativity In Nail Art Learning - Arista, Warsaditha Aprila; Maspiyah, Maspiyah; Nahari , Inty (Journal of Vocational Education Studies, 2025)
The objectives of this study are: 1. to evaluate the influence of project-based learning (PJBL) based on portfolio assessments on critical thinking skills in nail art learning and 2. Evaluate the influence of the project-based learning model (PJBL) based on portfolio analysis on the creative of students in the study of nail art. The procedure is complete. The sample of this study was 61 students at SMKN 1 Lingsar who were divided into experimental groups and control groups using cluster random sampling techniques. The data was collected through a multi-choice test for Critical Thinking skills and a rubric of analysis for creativity. The results showed that the PjBL model, based on portfolio evaluation, has a significant impact on students' critical thinking skills, with significance score of 0.024 and an N gain of 0.81 (high category). Moreover, this model also has a significant impact on student creativity, with a value score of 0.000 and an N gain of 0.85 (high category). Therefore, applying PjBL based portfolio analysis has been shown to be effective in improving students' critical thinking and creativity skills in learning nail art.